2023
DOI: 10.1371/journal.pone.0289413
|View full text |Cite
|
Sign up to set email alerts
|

Substance use, psychiatric symptoms, personal mastery, and social support among COVID-19 long haulers: A compensatory model

Abstract: Background Substance use has become a critical health concern during the COVID-19 pandemic, and emerging attention has been paid to people with the persistent symptoms of COVID-19 (COVID-19 long haulers) due to their high vulnerability. However, scant research has investigated their substance use and relevant psychosocial factors. The current study was to (1) examine substance use behaviors (i.e., legal drug use, illicit drug use, and non-medical use of prescription drugs); and (2) assessed their associations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Our results highly complement the previous MW intervention studies, where older adults (Yang & Conroy, 2018), breast cancer patients (Schröder et al, 2022), and community residents (Jones et al, 2021) have reported high acceptability to the MW intervention. Despite promising results, the various engagement across sessions suggest a need for personalized motivational strategies and addressing potential physical limitations to enhance future program engagement (Aggarwal et al, 2023).…”
Section: High Acceptabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Our results highly complement the previous MW intervention studies, where older adults (Yang & Conroy, 2018), breast cancer patients (Schröder et al, 2022), and community residents (Jones et al, 2021) have reported high acceptability to the MW intervention. Despite promising results, the various engagement across sessions suggest a need for personalized motivational strategies and addressing potential physical limitations to enhance future program engagement (Aggarwal et al, 2023).…”
Section: High Acceptabilitymentioning
confidence: 99%
“…Liu et al, 2010). Assessing the cost-effectiveness of these interventions in such settings, where healthcare resources are often limited, will be vital (Aggarwal et al, 2023;Mudiyanselage et al, 2023).…”
Section: The Need For Online Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Psychiatric symptoms frequently reported by these individuals have included depression, anxiety, sleep difficulties, fatigue, cognitive difficulties, and posttraumatic stress. [10][11][12] Although it is widely recognized that these psychiatric symptoms are common in PCC, establishing reliable estimates of their prevalence has been difficult. Numerous studies have reported high rates of patient-reported psychiatric symptoms in PCC.…”
Section: Introductionmentioning
confidence: 99%
“…Among the hundreds of symptoms described by people with PCC, psychiatric symptoms are prominent . Psychiatric symptoms frequently reported by these individuals have included depression, anxiety, sleep difficulties, fatigue, cognitive difficulties, and posttraumatic stress …”
Section: Introductionmentioning
confidence: 99%